2007
DOI: 10.1007/s10695-006-9120-7
|View full text |Cite
|
Sign up to set email alerts
|

Administration of a herbal immunoregulation mixture enhances some immune parameters in carp (Cyprinus carpio)

Abstract: The herbal immunoregulation mixture (HIRM) were extracts of several traditional Chinese medicines (TCMs): Astragalus membranaceus (from the root and stem), Polygonum multiflorum Thunb. (from the root), Isatis tinctoria L. (from the root), Glycyrrhiza glabra (from the stem). Immune parameters, which included macrophage phagocytic activity, macrophage reactive oxygen species (ROS), activity of serum lysozyme, nitric oxide synthetase (NOS) and superoxide dismutase (SOD), levels of total serum protein, globulin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 32 publications
4
27
1
Order By: Relevance
“…In this study, significant differences in SOD level were observed between experimental groups (P<0.05) and the highest SOD level was showed in the mixture of these three herbs group. However, unlike this study, Yuan et al (2007) noticed that there was no significant difference in SOD activity between the 0.5% and 1% herbal immune regulation mixture groups and the control group.…”
Section: Discussioncontrasting
confidence: 94%
“…In this study, significant differences in SOD level were observed between experimental groups (P<0.05) and the highest SOD level was showed in the mixture of these three herbs group. However, unlike this study, Yuan et al (2007) noticed that there was no significant difference in SOD activity between the 0.5% and 1% herbal immune regulation mixture groups and the control group.…”
Section: Discussioncontrasting
confidence: 94%
“…globulin and albumin [10][11][12]. Ginger as a phytobiotic is one of the most effective natural immune-stimulants [9].…”
Section: Introductionmentioning
confidence: 99%
“…Herbal drugs are known to possess immunomodulatory properties and generally act by stimulating both specific and non-specific immunity [146] [147] In the past few years the medicinal plants investigated for their immunostimulatory response on fish include Ocimum sanctum, Acalypha indica, Phyllanthus niruri, Phyllanthus emblica, Azadirachta indica, Crossandra infundibuliformis, Aloe vera, Curcuma longa, Solanum trilobatum, Piper betle, Murraya koenigi, and Mentha piperita [153], turmeric [20]; Chinese herbs Astragalus membranaceus, Polygonum multiflorum, Isatis tinctoria, Glycyrrhiza glabra, Lonicera japonica [154] [155], Massa medicata, Crataegi fructus, Scutelaria baicalensis, Artemisia capillaries, Cnidium officinale [156]. The immunomodulatory properties of Holi Basil, Tulsi (O. sanctum) have been studied in detail by many workers [157] [158] [159] [160], Das et al [144].…”
Section: As Immunostimulantmentioning
confidence: 99%
“…Chuntao et al [154] studied the response of a herbal immunoregulation mixture (HIRM) comprising of extracts of the following traditional Chinese medicines (TCMs): Astragalus membranaceus, Polygonum multiflorum, Isatis tinctoria, Glycyrrhiza glabra. The results showed that, compared with those in the control group, the diets with 0.5% and 1% HIRM resulted in significant increase in macrophage phagocytic activity, macrophage ROS and the levels of total protein, globulin, albumin and NOS activity in serum indicating that the herbal mixture elevated the immunity in carp (Cyprinus carp).…”
Section: As Immunostimulantmentioning
confidence: 99%